Multi Objective Service Selection Using Web Service Composition - Sudha, R (International Journal of Computer Sciences and Engineering, 2014)
The Web is a distributed, dynamic, and large information repository. However, a major drawback in this is that the Web contains much human consumable contents. The flaws that can be incurred are the user is ineffectual to incur his archetype data. To achieve an effective utilization of the multiple websites simultaneously, we go for Web services. Though, there are multiple web services available, the user is still inferior to his required data using a methodology called web service composition that facilitates users in accessing their desired services to retrieve their much required information to his need using queries. Genetic algorithms is used to adaptive heuristic search algorithms premised on the evolutionary ideas of natural selection used in solving various computational problems that demands optimization and adaptation to changing environments. Here, we provide access to multiple websites through web services where we can furnish all the required data.